Hypoglycemic Activity of Ruellia tuberosa Linn (Acanthaceae) in Normal and Alloxan-Induced Diabetic Rabbits: Hypoglycemic Activity of Ruellia tuberosa Linn - Durre Shahwar; Saif Ullah; Mobasher Ahmad; Sami Ullah; Naeem Ahmad; Muhammad Akmal Khan (Iranian Journal of Pharmaceutical Sciences, 2011)
The present study was carried out to determine the hypoglycemic activity of the methanolic extract and solvent fractions (n-hexane and ethyl acetate) of Ruellia tuberosa in normal and alloxan-induced diabetic rabbits. Optimum dose of R. tuberosa for hypoglycemic activity was determined by oral administration of the methanolic extract (ME) to normal and diabetic rabbits. Diabetes was induced by intra-peritoneal injection of alloxan monohydrate (150 mg/kg). Hypoglycemic effect of n-hexane (HF) and ethyl acetate (EF) fractions was evaluated at a dose of 150 and 100 mg/kg b.w., respectively, in normal and diabetic rabbits. Administration of the optimum dose (500 mg/kg b.w.) of R. tuberosa to normal and diabetic rabbits showed significant blood glucose lowering effect. EaF (100 mg/kg) showed the highest anti-diabetic activity with 28.64±0.28% decrease in blood glucose, while HF (150 mg/kg) showed moderate anti-diabetic activity and lowered the blood glucose level around 15.17±0.58%. The results were compared with the standard drug tolbutamide (100 mg/kg). Phytochemical investigation of EF and HF indicated flavonoids and triterpenoids in the extracts, respectively. Antioxidant activity was evaluated by DPPH method and the amount of total phenols was determined by Folin-Ciocalteu method. ME extract and its fractions showed the antioxidant activity in the order of EF>ME>WF>HF. The results were in agreement with the folkloric use of R. tuberosa in the treatment of diabetes and related complications.